2018
DOI: 10.3389/fnbeh.2018.00047
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of Cigarette Smoke Condensate Increases Glutamate Levels and Behavioral Sensitization

Abstract: Nicotine, a nicotinic acetylcholine receptor agonist, produces the reinforcing effects of tobacco dependence by potentiating dopaminergic and glutamatergic neurotransmission. Non-nicotine alkaloids in tobacco also contribute to dependence by activating the cholinergic system. However, glutamatergic neurotransmission in the dorsal striatum associated with behavioral changes in response to cigarette smoking has not been investigated. In this study, the authors investigated alterations in glutamate levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Nicotinic α4β2 receptors, on the other hand, have been implicated in obsessivecompulsive disorder and it has been shown that positive allosteric modulation of these receptors attenuated the obsessive behavior [38]. The actual behavioral effects of nAChRs are mediated by dopamine and glutamate and ultimately by GABAergic neurons [39,40]. Very recently, it was shown in rats that β2 nAChRs on dopamine neurons in the ventral tegmental area mediate nicotine's conditioned aversive effects, while those on GABA neurons mediate the conditioned rewarding effects [41].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinic α4β2 receptors, on the other hand, have been implicated in obsessivecompulsive disorder and it has been shown that positive allosteric modulation of these receptors attenuated the obsessive behavior [38]. The actual behavioral effects of nAChRs are mediated by dopamine and glutamate and ultimately by GABAergic neurons [39,40]. Very recently, it was shown in rats that β2 nAChRs on dopamine neurons in the ventral tegmental area mediate nicotine's conditioned aversive effects, while those on GABA neurons mediate the conditioned rewarding effects [41].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate was measured during Pavlovian fear conditioning and was transiently elevated around reward seeking in the basolateral amygdala (68). Glutamate also rose during exposure to repeated cigarette smoke and was highly correlated with psychomotor symptoms (69). Commercial glutamate biosensors are available, but they are not as popular as CFMEs for dopamine, so there are many future opportunities to explore glutamate dynamics.…”
Section: Glutamate Measurementsmentioning
confidence: 99%
“…Exposure to nicotine increases glutamate release in the dorsal striatum, NAc, ventral tegmental area, and prefrontal cortex by stimulating nAChRs [ 6 , 8 , 25 , 27 , 28 ]. However, repeated administration of 3R4F Kentucky reference cigarette smoke condensate (CSC) causes more prolonged and greater glutamate release in the dorsal striatum compared to nicotine alone [ 29 ]. These findings suggest that nicotine and non-nicotine alkaloids in cigarette smoke synergistically upregulate glutamatergic response in the brain reward system by hyperstimulation of nAChRs.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence shows that repeated administration of psychoactive drugs, such as nicotine, causes behavioral sensitization by increasing glutamate release in the dorsal striatum and NAc [ 6 , 8 ]. In our previous study, repeated administration of CSC produced more prolonged increase in glutamate release of the dorsal striatum and more hypersensitization of psychomotor behaviors compared to nicotine alone, which are highly correlated [ 29 ]. These findings suggest that altered glutamate concentrations in the striatum due to response to the combined effects of nicotine and non-nicotine compounds in cigarette smoke contribute to the hypersensitization of psychomotor activities.…”
Section: Introductionmentioning
confidence: 99%